2020
DOI: 10.1111/1541-4337.12527
|View full text |Cite
|
Sign up to set email alerts
|

Potential carcinogenic heterocyclic aromatic amines (HAAs) in foodstuffs: Formation, extraction, analytical methods, and mitigation strategies

Abstract: During the heat treatment of proteinaceous food, heterocyclic aromatic amines (HAAs), a kind of strong mutagens/carcinogens are formed. HAAs can be classified into two major groups based on the heating temperature, which are thermic HAAs generally formed in 150 to 300 °C and pyrolytic HAAs produced above 300 °C. This review focuses on the formation mechanisms of HAAs and identifies different mechanisms of the formation of HAAs in foodstuffs. Moreover, an overview of the available extraction, purification metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 177 publications
1
65
0
Order By: Relevance
“…Thus, several HPLC‐ESI‐MS/MS methods have been recently reported for the analysis of several HAAs in commercial meat products (Chang et al., 2019; Hsiao, Chen, & Kao, 2017; Jian, Yeh, Wang, Chen, & Chen, 2019) as well as roasted coffee (Xian et al., 2019) with good recoveries and sensitivity. LC methods couplet to high‐resolution mass spectrometry (HRMS) such as quadrupole time‐of‐flight mass spectrometry (q‐TOF‐MS) (Barceló‐Barrachina, Moyano, & Galceran, 2004), ion‐trap time‐of‐flight‐MS (LC‐IT‐TOF‐MS) (Ouyang, Li, Tang, Jin, & Li, 2015), and quadrupole‐Orbitrap HRMS (Q‐Orbitrap HRMS) (Dong, Xian, Li, Wu et al., 2020) allow obtaining accurate HRMS data for quantification operating in full MS mode, and product ion spectra for identification operating in data‐dependent or independent scan mode.…”
Section: Methods To Characterize Heterocyclic Aromatic Aminesmentioning
confidence: 99%
“…Thus, several HPLC‐ESI‐MS/MS methods have been recently reported for the analysis of several HAAs in commercial meat products (Chang et al., 2019; Hsiao, Chen, & Kao, 2017; Jian, Yeh, Wang, Chen, & Chen, 2019) as well as roasted coffee (Xian et al., 2019) with good recoveries and sensitivity. LC methods couplet to high‐resolution mass spectrometry (HRMS) such as quadrupole time‐of‐flight mass spectrometry (q‐TOF‐MS) (Barceló‐Barrachina, Moyano, & Galceran, 2004), ion‐trap time‐of‐flight‐MS (LC‐IT‐TOF‐MS) (Ouyang, Li, Tang, Jin, & Li, 2015), and quadrupole‐Orbitrap HRMS (Q‐Orbitrap HRMS) (Dong, Xian, Li, Wu et al., 2020) allow obtaining accurate HRMS data for quantification operating in full MS mode, and product ion spectra for identification operating in data‐dependent or independent scan mode.…”
Section: Methods To Characterize Heterocyclic Aromatic Aminesmentioning
confidence: 99%
“…Cooking meat at high temperatures may cause the formation of heterocyclic aromatic amines (HAAs) and polycyclic aromatic hydrocarbon (PAHs) in addition to advanced glycation end products (AGEs), which are associated with various potential health hazards, such as the increased risk of chronic diseases and several types of cancer. These contaminant compounds are traditionally extracted, identified, and characterised using chromatographic methods and mass spectrometry (Dong et al 2020;Sobral et al 2018;Zhang et al 2020b;Zhu et al 2020). Numerous studies have indicated that HAA, PAH, and AGE contents vary according to, among others, the heating method used for cooking meat, and that higher temperatures result in higher amounts of these compounds.…”
Section: Changes In Nutritional Qualitymentioning
confidence: 99%
“…Numerous studies have indicated that HAA, PAH, and AGE contents vary according to, among others, the heating method used for cooking meat, and that higher temperatures result in higher amounts of these compounds. Roasting, grilling, frying, and smoking are generally known to generate higher amounts of these contaminants compared to milder cooking methods (Dong et al 2020;Sobral et al 2018;Zhang et al 2020b).…”
Section: Changes In Nutritional Qualitymentioning
confidence: 99%
“…As an effective separation method, solvent extraction has been widely used in various industries, including wastewater treatment [5][6][7][8], pharmaceuticals [8][9][10] and food engineering [11,12]. Reliable liquid-liquid balance data plays an important role in the extraction and separation process and equipment design.…”
Section: Introductionmentioning
confidence: 99%